2007
DOI: 10.1021/bi700720e
|View full text |Cite
|
Sign up to set email alerts
|

Retrocyclin-2:  Structural Analysis of a Potent Anti-HIV θ-Defensin,

Abstract: Retrocyclins are circular mini-defensins with significant potential as agents against human immunodeficiency virus, influenza A, and herpes simplex virus. Retrocyclins bind carbohydrate-containing surface molecules such as gp120 and CD4 with high affinity (Kd, 10-100 nM), promoting their localization on cell membranes. The structural features important for activity have yet to be fully elucidated, but here, we have determined the first three-dimensional structure of a retrocyclin, namely, one of the most poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 40 publications
5
52
0
5
Order By: Relevance
“…In the case of RC2 the increased ability to self-aggregate could result in more effective cross-linking of cell membrane receptors through self-association on the cell surface. The increased aggregating activity of RC2 could also reflect a greater ability to form trimers or to self-associate once bound to viral particles (46). The finding of significant differences in antiviral activity between RCs or other defensins based on single amino acid changes is surprising, but not unprecedented (14,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of RC2 the increased ability to self-aggregate could result in more effective cross-linking of cell membrane receptors through self-association on the cell surface. The increased aggregating activity of RC2 could also reflect a greater ability to form trimers or to self-associate once bound to viral particles (46). The finding of significant differences in antiviral activity between RCs or other defensins based on single amino acid changes is surprising, but not unprecedented (14,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…These include four to six arginines plus six cysteines that form a tri-disulfide ladder cross-connecting their antiparallel ␤-strands (23,73). -Defensins kill bacteria (15,17), show broad-spectrum antiviral activity (5,21,74), and inhibit bacterial toxins, including anthrax lethal factor, a nonglycosylated zinc metalloprotease (75).…”
Section: Discussionmentioning
confidence: 99%
“…In such instances, carbohydrate epitopes of glycan chains afford likely biorecognition sites (19,20). The carbohydrate-binding ability of -defensins has been documented and examined with respect to their antiviral properties (21,22) and also because -defensins are among the smallest known lectins (23)(24)(25). Humans express six different ␣-defensins.…”
mentioning
confidence: 99%
“…NMR solution structures have shown that -defensins have a highly constrained symmetrical conformation made up of two antiparallel ␤-strands joined by two turns (Fig. 1b) (9,10). The three disulfide bonds are all on one face of the molecule with the cationic arginine side chains exposed on the other face (Fig.…”
mentioning
confidence: 99%